Flipped Classroom in Secondary Level English Language Teaching: Opportunities and Challenges - Timilsina, Pusparaj; Bhurtel, Sima (GS Spark: Journal of Applied Academic Discourse, 2025)
With the advancement of educational technology and changing context pedagogical approaches are shifting. The shift is occurring from teacher-centered models to students centered approaches. Among various teaching methodologies, a flipped classroom (FC) pedagogy involves inserting a designed course into a multitude of home assignments, such as videos, reading texts, podcasts, audio lectures, online quizzes, journal entries, and newspaper surveys. Thus, pre-class activities and lectures are viewed outside of class, and class time is devoted to active learning through activities such as demonstrations, group work, problem solving, and presentations. Among various methodologies and approaches, flipped classroom model is one of the most applied methodologies in academic field these days. This study was conducted to explore teachers’ perception and their experiences while teaching high school students in language classroom. This research work reports the understanding of flipped classroom pedagogy of six secondary-level English language teachers in Nepal by conducting narrative inquiry through semi-structured interviews that incorporates the opportunities and challenges faced by them. This research paper is assessed in connection with Alison King’s Constructionist Model. Teachers’ responses revealed that teachers recognize Flipped Classroom’s importance for increasing students’ learning interest and uplift autonomy. However, many teachers face challenges such as lack of technological access, constraints in curriculum and lack of teacher training. This study appeals the educators and policymakers to prioritize FC implementation in the context of Nepal in secondary-level education.